Selected problems associated with the treatment and care for patients with colostomy – part 1 - Muzyczka, Katarzyna; Kachaniuk, Hanna; Szadowska-Szlachetka, Zdzisława; Charzyńska-Gula, Marianna; Kocka, Katarzyna; Bartoszek, Agnieszka; Celej-Szuster, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2013)
The study presents a short historical background and practical application of intestinal ostomy as a treatment method of various intestinal disorders and injuries. Ostomy is a purposeful connection of the lumen of the intestine with abdominal integuments by surgery. After the surgical formation of the intestinal fistula, the patient must adjust to the new situation, gain basic knowledge and learn procedures of ostomy care. Thus, professional medical assistance is extremely important. The study aims to discuss basic notions concerning ostomy and ostomy equipment. Providing high-standard care and assistance for patients with ostomy requires both appropriate knowledge and practical skills.